2015
DOI: 10.1007/s00018-015-1839-9
|View full text |Cite
|
Sign up to set email alerts
|

Cellular factors modulating the mechanism of tau protein aggregation

Abstract: Pathological accumulation of the microtubule-associated protein tau, in the form of neurofibrillary tangles, is a major hallmark of Alzheimer’s disease, the most prevalent neurodegenerative condition worldwide. In addition to Alzheimer’s disease, a number of neurodegenerative diseases, called tauopathies, are characterized by the accumulation of aggregated tau in a variety of brain regions. While tau normally plays an important role in stabilizing the microtubule network of the cytoskeleton, its dissociation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 249 publications
0
57
0
Order By: Relevance
“…Previous studies reported that Tau is phosphorylated at the aforementioned sites by phospho‐kinases such as GSK3β, mitogen‐activated protein kinase (MAPK), and cyclin‐dependent kinase (CDK)5 (Fontaine et al ., 2015). Thus, we tested the increase in the concentration of these kinases in our experimental model 3 h after injection of monomers and oligomers of Aβ1‐42 in hTau mice.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that Tau is phosphorylated at the aforementioned sites by phospho‐kinases such as GSK3β, mitogen‐activated protein kinase (MAPK), and cyclin‐dependent kinase (CDK)5 (Fontaine et al ., 2015). Thus, we tested the increase in the concentration of these kinases in our experimental model 3 h after injection of monomers and oligomers of Aβ1‐42 in hTau mice.…”
Section: Resultsmentioning
confidence: 99%
“…There are several detailed reviews that cover structure, function, and post-translational modification of the tau protein (Fontaine et al , 2015; Lee and Leugers, 2012; Morris et al , 2011). Tau is encoded for by the MAPT gene found on chromosome 17, a gene that is mutated in several tauopathies including FTD (Ferrari et al , 2011) and PSP (Im et al , 2015).…”
Section: The Tau Protein – Functions and Dysfunctionsmentioning
confidence: 99%
“…Some of the cellular structures and proteins for which interaction of the respective domains has been suggested are designated by the arrows shown below. This scheme summarizes informations from several excellent reviews, from which more detailed descriptions of the different modifications and their effect on tau in addition to those mentioned in the text can be obtained: [8,9,10,11,12]. (B) Different oligomerization states of tau are shown.…”
Section: Tau Hyperphosphorylation and Its Relation To Admentioning
confidence: 99%
“…In addition to phosphorylation, tau is also subject to a number of other covalent modifications, such as ubiquitination, sumoylation, acetylation, and glycosylation, all affecting its biological activities [49,50] reviewed in [10].…”
Section: Posttranslational Modifications Influencing Tau Toxicitymentioning
confidence: 99%
See 1 more Smart Citation